GHRH-GH-IGF1 axis in pediatric Down syndrome: A systematic review and mini meta-analysis - Shaki, David; Hershkovitz, Eli; Tamam, Shai; Bollotin, Arkadi; David, Odeya; Yalovitsky, Guy; Loewenthal, Neta; Carmon, Lior; Walker, Dganit; Haim, Alon (Frontiers in Pediatrics, 2023)
Objective: To analyze and determine the quality of functioning in different components of GHRH-GH-IGF1 axis in children with Down Syndrome (DS). Design: Systematic review and mini meta-analysis of the literature. Methods: A search was performed in PubMed, Embase, Scopus, and PsycINFO through August 2022. Eligible studies included pediatric patients with DS who had undergone any laboratory evaluation of the GHRH-GH-IGF1 axis. Two reviewers independently screened articles for eligibility. Results of each type of test were weighed together in patients both with and without DS and were pooled using a random effects meta-analysis. Results: In total, 28 studies assessed the GHRH-GH-IGF1 axis function. A defect in three major components of GHRH-GH-IGF1 axis was found in a significant proportion of pediatric DS patients. Conclusions: A significant portion of short-stature pathogenesis in children with DS is associated with impaired GHRH-GH-IGF1 axis function